An Article Review on Teaching English in English, ‘in principle’: The National Language Curriculum for Japanese Senior High Schools - Yuniarti Yuniarti (ACCENTIA: Journal of English Language and Education, 2021)
This paper reviews the article written by Gregory Paul Glasgow entitled “Teaching English in English, ‘in principle’: The national language curriculum for Japanese senior high schools” published in 2014.  This paper aims to examine the author’ findings on teachers’ perception of new course of study by proposing some theoretical frameworks of communicative language teaching and the planned behavior analysis perspective to support the discussion. The article author raised the issue of Japanese English teachers’ perceptions towards the recently launched national foreign language curriculum for Japanese senior high schools including a provision of English classes to be conducted in English. The author tried to clear the issue by revealing how Japanese teachers of English (JTEs) interpreted the new initiative to conduct ‘English classes in English’ in Japanese senior higher schools and the relationship between official policy expectation and JTEs’ perceived new initiative in policy implementation.